Analisis Rasio Keuangan Daerah Dalam Mengukur Kinerja Keuangan Di BPKPD Kabupaten Buleleng - Made Risma Yuliani; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze regional financial ratios in measuring financial performance at BBPKPD Buleleng Regency in terms of effectiveness ratio, efficiency ratio, growth ratio, harmony ratio, and fiscal decentralization ratio. Quantitative descriptive is the method used in this research by sourcing primary and secondary data. Data collection methods and instruments used are interviews, literature studies, and documentation studies. The data analysis techniques used are descriptive statistics and ratio analysis. The results showed that in 2017-2023 the level of effectiveness ratio was ineffective, the efficiency ratio was efficient, the PAD growth ratio was not good, the compatibility ratio was not good, and the decentralization degree ratio was very good. This indicates that the level of PAD and financial management of BPKPD Buleleng Regency has not been running optimally and more special attention is needed in the realization of work programs so that the output or work achievements can produce maximum budget realization which will have an impact on PAD growth. Keywords : Regional Autonomy, Local Government Financial Performance, Ratio Analysis, Local Revenue